2013
DOI: 10.3399/bjgp13x665260
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Impact score: a new measure of public health effectiveness for general practices in England

Abstract: BackgroundHealth policy in the UK is increasingly focused on the measurement of outcomes rather than structures and processes of health care. AimTo develop a measure of the effectiveness of primary care in terms of population health outcomes. Design and settingA cross-sectional study of general practices in England. MethodTwenty clinical quality of care indicators for which there was evidence of mortality reduction were identified from the national Quality and Outcomes Framework (QOF) payfor-performance scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Each indicator was then weighted based on importance in terms of the estimated number of lives saved per 100,000 patients. These weights were derived from Ashworth et al, 85 who identified the highest level of evidence for risk reduction in all-cause mortality and converted risk reduction estimates into estimated mortality reduction rates per 100,000 population per annum (see Table 7 for details).…”
Section: Technical Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…Each indicator was then weighted based on importance in terms of the estimated number of lives saved per 100,000 patients. These weights were derived from Ashworth et al, 85 who identified the highest level of evidence for risk reduction in all-cause mortality and converted risk reduction estimates into estimated mortality reduction rates per 100,000 population per annum (see Table 7 for details).…”
Section: Technical Detailsmentioning
confidence: 99%
“…202,203 However, in sensitivity analysis we also examined 'reported achievement'. We started with a group of 20 QOF indicators, identified by Ashworth et al, 85 based on available evidence on mortality reduction. We then selected 16 out of the 20 indicators for which data were available throughout our period of analysis in a consistent format.…”
Section: Technical Detailsmentioning
confidence: 99%
See 3 more Smart Citations